Factors Contributing to the Successful Business of Street Market Food Vendors - Demong, Nur Atiqah Rochin; Kassim, Erne Suzila; Yunus, Noor’ain Mohamad; Shahrom, Melissa; Jailani, Sri Fatiany Abdul Kader (International Journal of Psychosocial Rehabilitation, 2020)
Micro-entrepreneurship plays an important role in the country’s economic development in generating the urban informal economy. Street market business can be classified as micro-entrepreneurship which in most cases the business has no employees besides the owner. High levels of unemployment and economic crisis led to the increasing number of street market vendor as a mean of survival and its ability to provide basic needs at affordable prices to the surrounding communities. This paper presents an analysis of the success factors contributing to the street market food vendors in selected street market in Malaysia. We highlight and identify some key factors that positively affect their sales revenue. A qualitative approach using focus group discussion method has been used to gain an in-depth understanding of success factors. Mini focus groups that intimate environment for discussion and explore more about sensitive issues of eight respondents have been conducted. Business success was measured by individual, environmental and organizational factors which can be divided into controllable and uncontrollable factors. Their results indicate that individual factors specifically business experience is an important success factors that positively affect sales revenue. The paper also comes to the conclusion that individual, environmental and organizational factors and government support were found positively and significantly related to the success of street market food business.